FORMATION OF STRENGTH ENDURANCE OF THE ABDOMEN AND BACK MUSCLES IN GIRLS WITH DEGREE I SCOLIOSIS USING FITBALL-GYMNASTICS - Anoshina T.V.; Tsinis A.V.; Fedotov D.M.; Shiryaeva T.P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the effect of fitball gymnastics on the indicators of static and dynamic strength endurance of the abdominal and back muscles in girls with grade I scoliosis. Methods and structure of the study. The scientific work involved 62 female students of a special medical health group at the age of 18.4±0.6 years with scoliosis of the 1st degree, who were divided into two subgroups depending on the organization of their training process at the university. The strength endurance of the abdominal and back muscles was assessed based on the results of exercises to hold the body and the number of lifts in various initial positions. Results and conclusions. It has been established that in the groups engaged in the framework of the author’s and standard methods of organizing physical culture lessons, there is a significant (p≤0.05) increase in results for all proposed tests. However, in the group that used fitball exercises, the increase in strength endurance is more pronounced. The author’s method of doing fitball gymnastics has a significant beneficial effect on the level of endurance of the abdominal and back muscles in girls with first-degree scoliosis.